A Ship Network Dynamic Routing Algorithm Based on Vector Network - Zhao, Jianguang; Fan, Jingjing (Polish maritime research, 2018)
In view of the characteristics of low speed mobile ship network, strong network dynamics and large signal interference, this paper proposes a low-rate mobile sensor network routing algorithm. In mobile wireless sensor networks, network topology changes frequently is a new challenge for resource constrained sensor node. Constantly updated network topology, sensor nodes need to exchange data frequently in order to maintain fresh route, resulting in sensor nodes consume a lot of energy. To solve this problem, to reduce control overhead is considered to be an effctive strategy. In this paper, we present a vector network-based dynamic routes (VNDR) scheme aims to minimize the control cost of the sensor nodes. We propose data exchange based on binary-coded vector address to reduce the control cost, moreover, we present a set of communication rules that govern the routes search procedure thereby requiring little cost of packet analysis to determine the next hop of node. VNDR performance was compared with well known scheme such as SPIN and DD. Simulation results show that, our VNDR scheme reduced the network control overhead and improved network lifetime.